PENGARUH PEMBELAJARAN DESAIN GRAFIS BERBASIS PHOTOSHOP TERHADAP MINAT BELAJAR SISWA PADA MATA PELAJARAN MULTIMEDIA KELAS X - Fricticarani, Ade; Rini, Ratu Yustika; Dayurni, Popi; Rosdiana, Ana (Jurnal Inovasi dan Teknologi Pendidikan, 2023)
This thesis discusses the Effect of Photoshop-Based Graphic Design Learning on Student Interest in Multimedia Subject Class X at SMK Al-Falah Pandeglang. Lack of student interest in graphic design, the researchers aimed to conduct research with the title The Effect of Photoshop-Based Graphic Design Learning on Student Interests in Multimedia Subject Class X at Al-Falah Vocational School. The sample in this study was 25 students. It is a quantitative research with survey method, data collection technique by observation, survey, interview and documentation. Data collection is done by using a questionnaire. The results showed that there was a significant effect of the correlation coefficient r of 0.718 (70.18%) at an average interval of 0.60-0.799. This means that the variable X (Influence of Photoshop-Based Graphic Design Learning) has an effect on the Y variable (Students' Learning Interest). The results of the study can be concluded that there is an influence. Researchers highly recommend this research can be continued by further researchers